2014
DOI: 10.1038/ismej.2014.81
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Thaumarchaea, Nitrospira and methanotrophs modulate autotrophic nitrification in volcanic grassland soil

Abstract: Ammonium/ammonia is the sole energy substrate of ammonia oxidizers, and is also an essential nitrogen source for other microorganisms. Ammonia oxidizers therefore must compete with other soil microorganisms such as methane-oxidizing bacteria (MOB) in terrestrial ecosystems when ammonium concentrations are limiting. Here we report on the interactions between nitrifying communities dominated by ammonia-oxidizing archaea (AOA) and Nitrospira-like nitrite-oxidizing bacteria (NOB), and communities of MOB in control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
72
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 71 publications
8
72
0
Order By: Relevance
“…It is therefore plausible to attribute the ammonia oxidation indirectly observed via net nitrification in the NA microcosms to the activity of AOA well in line with a previous DNA-SIP study attributing ammonia-oxidation exclusively to Thaumarchaea in the same soil (Daebeler et al 2014). This is in contrast to many other soils where AOB are suggested to have a more important role in nitrification than AOA (e.g.…”
Section: Effect Of Ammonium Addition To Soil Microcosmssupporting
confidence: 87%
“…It is therefore plausible to attribute the ammonia oxidation indirectly observed via net nitrification in the NA microcosms to the activity of AOA well in line with a previous DNA-SIP study attributing ammonia-oxidation exclusively to Thaumarchaea in the same soil (Daebeler et al 2014). This is in contrast to many other soils where AOB are suggested to have a more important role in nitrification than AOA (e.g.…”
Section: Effect Of Ammonium Addition To Soil Microcosmssupporting
confidence: 87%
“…Studying these features in an environmental context will be important to identify microbial interaction partners of AOA (for example, specific associations with nitrite oxidizers or other groups that could participate in the process of nitrogen species interconversions connected through the substrate-product chain) (90). It will be equally interesting to elucidate those adaptations that are the basis for the enormous ecological success of AOA in terrestrial environments.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of Nitrobacter genome sequences provided first insights into the genomic makeup of NOB and revealed a greater metabolic flexibility than anticipated earlier, which included the mixotrophic utilization of various organic substrates (8,9). However, Nitrobacter require high nitrite concentrations (10,11), and molecular surveys indicated that Nitrobacter are not the primary NOB in ecosystems with low ambient nitrite levels such as unfertilized soils (12), freshwater habitats (13), and most WWTPs (14).…”
mentioning
confidence: 99%